2000
DOI: 10.1046/j.1365-263x.2000.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of treatment provided in the primary and secondary care services for children attending a dental hospital following complicated crown fracture in the permanent dentition

Abstract: Emergency treatment of complicated crown fractures, particularly in primary care services is often inappropriate or inadequate with regard to emergency management of the exposed pulp and provision of a hermetic coronal seal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 13 publications
1
40
0
Order By: Relevance
“…A review of the literature revealed that while there is agreement that early treatment (within 24 h) is crucial for the success of a cervical pulpotomy , there is no consistency in the opinions regarding the effect of treatment delay of Cvek pulpotomies. Some authors have suggested that the time elapsing from the fracture to pulpotomy, followed by coronal restoration of the exposed pulp and dentinal tubuli, was important to minimize the possibility of microbial pulp invasion, thus ensuring pulp and periodontal healing . Others have suggested that the time between injury and treatment has limited influence on the long‐term outcome of partial pulpotomy, and therefore, the treatment of an exposed pulp due to trauma in a permanent tooth does not need not take place on the same day as the injury ().…”
Section: Time Factormentioning
confidence: 99%
“…A review of the literature revealed that while there is agreement that early treatment (within 24 h) is crucial for the success of a cervical pulpotomy , there is no consistency in the opinions regarding the effect of treatment delay of Cvek pulpotomies. Some authors have suggested that the time elapsing from the fracture to pulpotomy, followed by coronal restoration of the exposed pulp and dentinal tubuli, was important to minimize the possibility of microbial pulp invasion, thus ensuring pulp and periodontal healing . Others have suggested that the time between injury and treatment has limited influence on the long‐term outcome of partial pulpotomy, and therefore, the treatment of an exposed pulp due to trauma in a permanent tooth does not need not take place on the same day as the injury ().…”
Section: Time Factormentioning
confidence: 99%
“…This fi nding would appear to be corroborated by a number of previous studies which all have highlighted the lack of confi dence and competence in trauma management among UK dentists. [20][21][22] Indeed these previous papers have all called for an increase in trauma-related teaching within undergraduate and postgraduate dental curricula. The implications of poor trauma management are considerable with far-reaching economic, psychosocial and oral health consequences for the patient.…”
Section: Confi Dence In Relation To Trauma Managementmentioning
confidence: 99%
“…The majority of dental trauma cases seen in secondary care present initially in general dental practice 1 and mainly occur in children. It is therefore imperative that general dental practitioners (GDPs) have a sound working knowledge of managing dental trauma; especially the initial treatment.…”
Section: Introductionmentioning
confidence: 99%